(untitled) (Scientific journal of the Fergana State University, 2023)
This article talks about authentic texts that they are rich in socio-cultural lacunae and intercultural approach, socio-cultural lacunae are a special layer of the verbal-semantic and cognitive thesaurus of the language. The lacuna appeared in a specific situation, as a result of clarifying the semantic structure of the word, the elimination of the lacuna with the help of interpreting the word, the process of perceiving and understanding authentic texts was explained in examples.